ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENJUALAN BATIK SAAT MASA PANDEMI COVID 19 DI KOTA KLATEN - Alvin Adam; Rosita (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to look at the decline in economic activity in terms of sales due to the corona virus (COVID-19). with the aim of seeing the sales made by the fashion industry, especially in the sale of batik in Klaten City. Many SME business actors experience a decrease in profit or sales turnover. This is because the government enforces social distancing, so offline sales are very limited. This research on the effect of Covid-19 on the sale of batik uses a quantitative method, which is based on numbers using statistical tools. Respondents from this study amounted to 31 respondents in the Klaten area. Capital states if there is no influence between capital and sales. Quality negatively affects sales. Competition has a positive effect on sales. Promotion in this study has no impact on sales. The results of this study indicate that not all variables have a significant influence on Batik sales in the city of Klaten. . It can be said if Capital, Quality, Promotion have no effect on the sale of a product owned by the company / SME. While the competition variable has an effect on sales.